Proteogenomics Reveals Enriched Ribosome Assembly and Protein Translation in Pectoralis major of High Feed Efficiency Pedigree Broiler Males - Bottje, Walter G.; Lassiter, Kentu; Piekarski-Welsher, Alissa; Dridi, Sami; Reverter, Antonio; Hudson, Nicholas J.; Kong, Byung-Whi (Frontiers in Physiology, 2017)
Background: In production animal agriculture, the cost of feed represents 60 to 70% of the total cost of raising an animal to market weight. Thus, development of viable biomarkers for feed efficiency (FE, g gain/g feed) to assist in genetic selection of breeding stock remains an important goal in commercial breeding programs. Methods: Global gene (cDNA microarray, RNAseq) and protein expression (shotgun proteomics) analyses have been conducted on breast muscle samples obtained from pedigree broiler males (PedM) exhibiting high and low FE phenotypes. Using the entire datasets (i.e. no cutoffs for significance or fold difference in expression) the number of genes or proteins that were expressed numerically higher or lower in the high FE compared to the low FE phenotype for key terms or functions, e.g. ribosomal, mitochondrial ribosomal, tRNA, RNA binding motif, RNA polymerase, small nuclear ribonucleoprotein, and protein tyrosine phosphatase, were determined. Bionomial distribution analysis (exact) was then conducted on these datasets to determine significance between numerically up or down expression. Results: Processes associated with mitochondrial proteome expression (e.g. mitochondrial ribosomal proteins, mitochondrial transcription, mitochondrial tRNA, and translation) were enriched in breast muscle from the high FE compared to the low FE pedigree male broiler phenotype. Furthermore, the high FE phenotype exhibited enrichment of ribosome assembly (e.g. RNA polymerase, mitochondrial and cytosolic ribosomes, small and heterogeneous nuclear ribonucleoproteins), as well as nuclear transport and protein translation processes compared to the low FE phenotype. Quality control processes (proteosomes and autophagy) were also enriched in the high FE phenotype. In contrast, the low FE phenotype exhibited enrichment of cytoskeletal proteins, protein tyrosine phosphatases, and tyrosine kinases compared to the high FE phenotype. These results suggest that processes of mitochondrial and cytosolic ribosomal construction, activity, and protein translation would be enhanced in high FE breast muscle, and that phosphorylation of tyrosine moieties of proteins could be prolonged in the high compared to low FE phenotype. The results indicate the presence of a proteogenomic architecture that could enhance ribosome construction, protein translation and quality control processes and contribute to the phenotypic expression of feed efficiency in this PedM broiler model.